Faktor-Faktor yang Mempengaruhi Intensi Anggota Tim untuk Melakukan Knowledge Sharing dalam Proyek Pengembangan Software di PT Gamatechno Indonesia - , Endar Kusmarwanto, S. T ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to find out what factors are able to influence intention to share knowledge in software development project at Gamatechno and to find out level of project team memberâs intention to share knowledge. A framework based on the theory of planned behavior used as a reference in the study. Qualitative approach with exploratory research was selected for the collection and analysis of data. Data collection techniques perform by interviews of eleven informants directly involved and know the ins and outs of knowledge sharing in software development project at Gamatechno. From the research results can be seen that eight factors influence team memberâs intention to share knowledge in software development project at Gamatechno: team success, learning process, reward, expectations of sharing, available resources, competency, work pressure, and regulation. Team member of software development project at Gamatechno has good enough intention to share knowledge.